Integrating technology, ethnomathematics, and realistic mathematics education in learning statistics: A learning trajectory - Nursyahidah, Farida; Wardono, Wardono; Mariani, Scolastika; Wijayanti, Kristina (IKIP Siliwangi and I-MES, 2025)
Statistics is a critical subject for developing students' academic and career competencies, yet it remains challenging for many students due to its abstract nature. To address this issue, a study was conducted to design a learning trajectory for teaching statistical concepts by integrating technology, ethnomathematics, and realistic mathematics education (TE-RME) within the culturally relevant context of pranata mangsa, a traditional Javanese calendar system. Employing a design research methodology, the study involved 32 eighth-grade students from a junior high school in Semarang, Indonesia. It was conducted in three phases: preparation for the experiment, designing learning activities, and retrospective analysis. The resulting learning trajectory consisted of three structured activities: observing pranata mangsa videos to collect and present data, deriving formulas for measures of central tendency, and exploring methods for calculating data dispersion. Findings indicated that the integration of pranata mangsa in the TE-RME framework significantly enhanced students' understanding of statistical concepts by connecting abstract ideas to culturally meaningful contexts. This approach facilitated quicker and more meaningful learning, demonstrating the effectiveness of incorporating local wisdom into mathematics education. The study also highlights the potential for future research to explore other culturally relevant contexts to teach mathematical concepts, further advancing the field of culturally responsive education.